PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN MEMAKAI JASA CV. CATERING REZEKI DI KOTA PALU - Badjamal, Faigah A. (Katalogis, 2018)
The purpose of this research 1). To find out the mix consisting of products, prices, and places simultaneously has a significant effect on consumers’decisions to use the services of CV.Catering Rezeki in Palu. 2) to find out which variables have partially dominant influence on consumer decisions to use services of CV.Catering Rezeki in Palu. This research is a descriptive-verification study to describe the results of the data obtained by involving 60 respondents with a population of all consumers who use the services of CV.Catering Rezeki in Palu. Data collection techniques using the estimation method and interpretation of the results then the ideal and respresetative sample size is dependent on the number of variables multiplied by 15 to 20. The minimum sample for this study which has 4 independent variables is 4 x 15 = 60 people. Data processing using the statiscal product and service solution program (spss 19.0), after doing a statistical test using multiple linear regression analysis, the results of the study show 1). Marketing mix consisting of products, prince, promosion and place simultaneously have a significant effect on consumer decisions using CV.Catering Rezeki in Palu services 2). Product variabels that have a dominant influence persistently on the decision to use CV.Catering services in Palu.